Effects of DTX3L on the cell proliferation, adhesion, and drug resistance of multiple myeloma cells - Yaodong Shen; Yuxiang Sun; Linlin Zhang; Hong Liu (Tumor Biology, 2017)
Cell adhesion–mediated drug resistance is an important factor that influences the effects of chemotherapy in multiple myeloma. DTX3L, a ubiquitin ligase, plays a key role in cell-cycle-related process. Here, we found that the expression of DTX3L gradually increased during the proliferation of myeloma cells, which resulted in arrest of the cell cycle in the G1 phase and promoted the adherence of myeloma cells to fibronectin or bone marrow stromal cells. In addition, silencing of DTX3L improved sensitivity to chemotherapy drugs in multiple myeloma cell lines adherent to bone marrow stromal cells and increased the expression of caspase-3 and poly-adenosine diphosphate-ribose polymerase, two markers of apoptosis. Finally, we also found that DTX3L expression was regulated by focal adhesion kinase. Taken together, the results of this study show that DTX3L plays an important role in the proliferation and cell adhesion–mediated drug resistance of multiple myeloma cells and as such may play a key role in the development of multiple myeloma.